Analysis of North Bandung Area (KBU) Punclut Cidadap District, Bandung City Based on Land Management - Yohanna Melianti; Dadang Epi Sukarsa; Betty Rubiati (JURNAL AKTA, 2024)
The Northern Bandung Area in Punclut, Cidadap District, from the 1960s to the 1980s, based on state land, certificates of land rights were issued without land consolidation. These certificates were then given to cultivators by the state, who subsequently engaged in buying and selling transactions. These transactions continued, resulting in the development of residential areas, cafes, restaurants, or commercial centers that do not comply with land use regulations. Land use policy is implemented for land parcels that have rights, whether registered or not, including state land and customary land according to applicable laws and regulations. The research method used is normative juridical, which relies on literature review dominated by secondary data, including primary legal materials, secondary legal materials, and tertiary legal materials. The research findings indicate that decisions and policies have been made for the Northern Bandung Area, but they have not been optimally implemented in practice, leading to massive development in the area such as residential areas, cafes, restaurants, or commercial centers. However, land use is synonymous with land utilization, where urban land utilization should guarantee the community against pollution, thereby creating a healthy environment, both physically and spiritually. Continuous deviations from these principles will inevitably result in an unhealthy environment, both physically and spiritually.